Audit Opinion Accuracy, Corporate Governance and Downward Auditor Switching: A Study of Association of Southeast Asian Nations Economics Community - Budisantoso, Totok; Rahmawati, Rahmawati; Bandi, Bandi; Probohudono, Agung Nur (International Journal of Economics and Financial Issues, 2017)
Objective of this research is to examine moderating effect of audit opinion accuracy on relationship between corporate governance and downward auditor switching in five countries of Association of Southeast Asian Nations (ASEAN) region. Sample of this research is manufacture companies listed in stock exchange of Indonesia, Malaysia, Singapore, Thailand and Philippine. Based on country fixed effect logistic regression, results show that audit committee, independent commissioner and financial deepening have negative effect on downward auditor switching, if opinion accuracy is high. It indicates that monitoring role of audit committee, independent commissioner and public will increases audit quality by prevent high quality auditor, especially when opinion accuracy is high. In the other hand, opinion accuracy does not moderate effect of ownership on downward auditor switching, indicates that there is entrenchment effect of controlling shareholder in auditor switching decision. Keywords: Audit Opinion Accuracy, Corporate Governance, Downward Auditor Switching, ASEAN JEL Classifications: M42, G32, G34